Zoonotic potential of health wild felids for dermatophytes - Figueiredo, Mayra A.P. [UNESP] (2014)
Dermatophytes are fungi that cause superficial mycoses in animals and humans. Infection can occur through direct contact with spores or hyphae of contaminated material. Studies in asymptomatic domestic cats have demonstrated the presence of dermatophytes which make them significant source of infection for other animals and humans that aspect is not well studied in wild felines. This study aimed to determine the presence of dermatophytes on the haircoat of health wild felids kept in captivity in Screening Center for Wild Animals in Sao Luis City, Maranhao State, Brazil. Hair samples of 13 adults wild felines were collected, seven Leopardus trigrinus (5 males and 2 females), one Leopardus wiedii (female) and five Leopardus pardalis (2 males and 3 females) and seeded by printing on Sabouraud dextrose agar plates supplemented with chloramphenicol 0.5 g L-1 cycloheximide and 0.4 g L-1 at 25°C with daily observation for 15 days. For the analysis of reproductive forms were stained with Giemsa for 35 min. In cultures was isolated: Microsporum canis, Trichophyton mentagrophytes and Epidermophyton floccosum. The occurrence of dermatophytes on the haircoat of healthy wild felids kept in captivity, confirms its status as asymptomatic carriers and characterizes them as sources of infection for other animals including humans.